Carbonic anhydrase-related protein CA10 is an evolutionarily conserved pan-neurexin ligand - Sterky, Fredrik H. (Proc Natl Acad Sci U S A, 2017)
Establishment, specification, and validation of synaptic connections are thought to be mediated by interactions between pre- and postsynaptic cell-adhesion molecules. Arguably, the best-characterized transsynaptic interactions are formed by presynaptic neurexins, which bind to diverse postsynaptic ligands. In a proteomic screen of neurexin-1 (Nrxn1) complexes immunoisolated from mouse brain, we identified carbonic anhydrase-related proteins CA10 and CA11, two homologous, secreted glycoproteins of unknown function that are predominantly expressed in brain. We found that CA10 directly binds in a cis configuration to a conserved membrane-proximal, extracellular sequence of α- and β-neurexins. The CA10–neurexin complex is stable and stoichiometric, and results in formation of intermolecular disulfide bonds between conserved cysteine residues in neurexins and CA10. CA10 promotes surface expression of α- and β-neurexins, suggesting that CA10 may form a complex with neurexins in the secretory pathway that facilitates surface transport of neurexins. Moreover, we observed that the Nrxn1 gene expresses from an internal 3′ promoter a third isoform, Nrxn1γ, that lacks all Nrxn1 extracellular domains except for the membrane-proximal sequences and that also tightly binds to CA10. Our data expand the understanding of neurexin-based transsynaptic interaction networks by providing further insight into the interactions nucleated by neurexins at the synapse.